Model predictive control for current balancing in a four-phase buck converter - Yahaya J.A.F.; Mansor M. (International Journal of Renewable Energy Research, 2023)
Boost converter; Buck converter; Controllers; Electric inverters; Linear control systems; MATLAB; Model predictive control; Predictive control systems; Buck converters; Buck topology; Current balancing; Current controller; Four-phase; Model-predictive control; Multiphase DC-DC; Multiphases; Renewable energies; Superposition theorem; Lithium-ion batteries